Development of a Psychological Well-Being Instrument in Secondary Schools - Romi Fajar Tanjung; Sigit Dwi Sucipto; Yola Eka Putri; Abelia Agustin; Citra Finky Lestary; Nabila (Bisma The Journal of Counseling, 2025)
Psychological well-being is a crucial psychological condition that every individual should possess, as a high level of psychological well-being contributes significantly to the overall course of a person’s life. The purpose of this study is to develop a psychological well-being instrument that can be used to identify an individual’s psychological well-being condition. This research employed a Research and Development (R&D) approach using the 4D design model. The respondents of this study consisted of 129 high school students. Data analysis for the instrument development utilized Aiken’s V, Pearson’s product-moment correlation, and Cronbach’s Alpha. The results of the study produced a valid psychological well-being instrument consisting of 48 items and a reliable coefficient with a Cronbach’s Alpha value of 0.876. The implication of this instrument development, in general, is that educators and educational practitioners can accurately identify students’ psychological well-being conditions through the administration of this instrument. Specifically, for school counselors, the data can serve as an initial reference for planning guidance and counseling programs or providing follow-up interventions for students with low levels of psychological well-being.